Electrochemical immunosensor based on gold-thionine for detection of subarachnoid hemorrhage biomarker - Wang, Mengyue; Gao, Feng; Ni, Shoujie; Song, Yanan; Wang, Cai; Li, Qian; Zhao, Peng (Frontiers in Bioengineering and Biotechnology, 2023)
The establishment of a direct, rapid and ultra-sensitive detection method based on electrochemical biosensors has emerged as a new competitive challenge in disease biomarkers research. In this study, a novel free-labeled electrochemical immunosensor for rapidly and sensitively detecting IL-6 in subarachnoid hemorrhage (SAH) blood has been developed using Au nanospheres-thionine composites (AuNPs @ THI) as the interface modified on the electrode. To this end, AuNPs with a high surface area and biocompatibility are capable of providing abundant biomolecular binding sites for conjugating antibodies. Additionally, because of the electroactive groups in the molecular structure, THI possesses excellent chemical reversibility and stability, as well as the ability to transfer electrons quickly, which significantly amplifies the current signal and further effectively enhances the sensitivity of the immunosensor. Under the best conditions, the developed electrochemical immunosensor exhibited a wide linear range from 10-2 ng/mL to 102 ng/mL with a low detection limit of 1.85 pg/mL. Furthermore, when the immunosensor was employed in the analysis of IL-6 in 100% serum, the results obtained by electrochemical immunoassay were consistent with those obtained by enzyme-linked immunosorbent assay (ELISA) without suffering from other significant biological interference. As a result, the positive results demonstrated that our developed electrochemical immunoassay has a high potential for use in the clinical diagnosis of SAH.